2017
DOI: 10.1017/s0266462317000113
|View full text |Cite
|
Sign up to set email alerts
|

Secure Internet of Things-Based Cloud Framework to Control Zika Virus Outbreak

Abstract: The cloud-based proposed system contributed to the accurate NBN-based classification of infected users and accurate identification of risk-prone areas using Google Maps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 18 publications
0
27
0
2
Order By: Relevance
“…Zika virus (ZikaV) is currently one of the most important emerging viruses in the world that have caused outbreaks and epidemics and has also been associated with severe clinical manifestations and congenital malformations. Sanjay Sareen et al [8] introduced a cloud-based system for detecting and controlling the ZikaV using a mobile device. The authors in the article [9] presented and identified the different ways to implement the edge computing paradigm, by using M2M communications in dense networked systems via social connectivity from two different perspectives: the offered reliability for delay-tolerant (delaysensitive) services and the energy conservation over reliability provision.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zika virus (ZikaV) is currently one of the most important emerging viruses in the world that have caused outbreaks and epidemics and has also been associated with severe clinical manifestations and congenital malformations. Sanjay Sareen et al [8] introduced a cloud-based system for detecting and controlling the ZikaV using a mobile device. The authors in the article [9] presented and identified the different ways to implement the edge computing paradigm, by using M2M communications in dense networked systems via social connectivity from two different perspectives: the offered reliability for delay-tolerant (delaysensitive) services and the energy conservation over reliability provision.…”
Section: Literature Reviewmentioning
confidence: 99%
“…So if the symptoms persist more than 7 days the person has to check for early prediction method that is using our proposed method. If they found to be infected that person has to go for a RNA test in which it is completely analyzed [19] [20]. Otherwise no need to go for any other test.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Using the LR-Linear Regression the specificity 69%, Sensitivity is 68, accuracy is 65 [21]. For NN the specificity 85%, Sensitivity is 84, accuracy is 83 [22] and for NBN the specificity 73%, Sensitivity is 80, accuracy is 87 [20]. Finally the MLP our proposed classifier gives the result of specificity 97%, Sensitivity is 98, and accuracy is 97.9.…”
Section: Figure 5: Comparsion Of Lr Nn Nbn Mlpmentioning
confidence: 99%
“…It introduces the facility of local processing leading to reduction in data size, lower latency, high throughput and power efficiency of the cloudbased systems. Fog computing technology has been successfully implemented in smart cities [31] and healthcare [23,22,42,49,50,51]. Fog devices are embedded computers such as Intel Edison or Raspberry Pi that acts a gateway between cloud and mobile 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 devices.…”
Section: Fog Computingmentioning
confidence: 99%